An annotated type catalogue of earwigs (Dermaptera) in the Zoological Museum Hamburg (ZMH) - Nguyen, Eileen; Matzke, Danilo; Federspiel, Miriam; Peters, Carolin; Husemann, Martin (Zootaxa, 2025)
The entomological collections of the Zoological Museum Hamburg (ZMH) contain one of the largest collections of earwigs (Dermaptera) in Germany, including many types. In total 312 species are housed in the collection with about 3200 individuals. The collection contains 74 type specimens, including 10 holotypes, 24 paratypes, 5 paralectotypes, and 35 syntypes belonging to 24 species (19 valid taxa and 5 synonyms).